A radiographic retrospective study using CBCT on supernumerary root (radix entomolaris and paramolaris) among KOD IIUM patients - Mohamad Noor, Faqihah Adlina; Mohamad Shukri, Nur’akmal Nabilah; Kusumawardani, Anisa; Sukmasari, Susi; Ghazali, Ahmad Badruddin (2020)
Introduction: Radix entomolaris (RE) referred to supernumerary root located at distolingual side, while radix paramolaris (RP) is mesiobucally located. This study was conducted to determine the prevalence of RE and RP among KOD IIUM patients and to record the differences in genders, races and sides by using Cone Beam Computed Tomography (CBCT). Materials and Methods: 506 CBCT of mandibular first and second molar with complete root formation were collected and interpreted from Romexis software. Inter and intra-observer reproducibility for all interpreters were done with Kappa value 1.00. Races, genders, occurrence sides of RE and RP were recorded and analyzed by using Chi-square test and Fisher’s exact test. Results: RE and RP prevalence was 15% and 0.6% respectively. The prevalence of RE according to races (Malay 10.5%, non-Malay 4.3%), sides (right 38%, left 39.2%, both 17.7%) and gender (female 9.3%, male 5.5%).The prevalence of RP according to sides (right 2.5%, left 0%, both 1.3%), gender (female 0.4%, male 0.2%) and races (Malay 0.6%, non-Malay 0%). The RE differences between genders and races were significant (p<0.05), while RE differences between sides and RP differences between gender, sides and races were insignificant (p>0.05). Conclusion: RE occurred more frequent compared to RP. Both RE and RP were higher in Malay and females. RE mostly found on left sides while RP was higher on right sides. The differences of RE between genders and races were significant. Clinician should be equipped with sound knowledge of root canal morphology in order to facilitate the endodontic treatment.